Improving PAI Learning Outcomes in Class IV by Using the Indexcard Match Method at SDN 10 Koto Nopan Saiyo - Edi Syukri (BiCED Proceeding, 2024)
This study aims to improve learning outcomes and student engagement in the Islamic Religious Education (PAI) subject for grade IV students at SDN 10 Koto Nopan Saiyo through the implementation of problem-based and project-based learning methods. The focus of the study is on teaching QS Al-Hujurat verse 13 and the obligatory and impossible attributes of Prophets and Messengers. The research employs a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The study involved 12 grade IV students from SDN 10 Koto Nopan Saiyo. The findings indicate a significant improvement in learning outcomes and student engagement from cycle I to cycle II. In cycle I, the average student engagement was 62%, and the learning mastery was 25%. In cycle II, the project-based approach increased the average student engagement to 96%, with a learning mastery of 100%. In conclusion, the gradual implementation of problem-based and project-based learning methods significantly enhances learning outcomes and student engagement. This strategy is recommended to foster an active, creative, and meaningful learning environment in PAI education.